Sosialisasi: Manfaat E-commerce Untuk Meningkatkan Penjualan Pada UMKM Obat - Soetiyani, Ari; Lukiyana, Lukiyana; Ariandi, Ariandi; Kamaruddin, Muhammad Junaid; Jundi, Musthofa (Penerbit Goodwood, 2024)
E-commerce is a form of information technology development, which is a sales medium that provides positive things, and makes the shopping process effective and efficient. However, not all MSME actors, especially MSMEs in Medicine, use e-commerce to sell their products. This socialization was carried out as a community service program in the form of providing knowledge about the benefits of e-commerce, with the aim of drug SMEs being able to understand and utilize e-commerce as a sales medium that would be able to increase income for the MSMEs themselves. The population in this socialization activity is MSME actors in the Kelapa Gading area, North Jakarta with a sample of 15 MSME actors. The method used is a lecture related to the importance of e-commerce by students of the University of 17 August 1945 Jakarta accompanied by a supervisor. Parameters for evaluating the success of this socialization using the Pre-Test and Post-Test questionnaires. The expected result is an increase in the breadth of insight into the knowledge of MSME actors on the benefits of e-commerce and being able to apply e-commerce as a sales medium.